Nano copper oxide catalyst as well as preparation method and application thereof

Modify the nano -CUO catalyst prepared through the CEO2 prepared by the water thermal method. By introducing high -ion and ions to achieve multiple lattice distortion of copper -oxide, the catalyst with oxygen vacancy is generated to solve the thermal stability and catalytic performance of the CU base catalyst. Insufficient problems have achieved efficient methanol conversion and low CO selectivity.

CN119346124AActive Publication Date: 2025-01-24HUNAN UNIV

Patent Information

Application Number
CN202411557054.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-24
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

Existing Cu-based catalysts have problems with insufficient thermal stability and catalytic performance in methanol steam reforming (MSR) reactions, especially the nano Cu particles are prone to agglomeration and sintering.

Method used

Nano-copper oxide particles and soluble cerium salts are reacted through a hydrothermal method in a vacuum or protective atmosphere to partially reduce the copper oxide on the surface of the copper oxide to silver oxide, and introduce coating cerium oxide and hydrazine to realize the formation of the copper oxide crystal lattice. Multiple lattice distortions generate nano-copper oxide catalysts rich in oxygen vacancies.

Benefits of technology

It improves the thermal stability and catalytic performance of the catalyst, realizes nearly 100%methanol conversion rate and 0.045%CO selectivity, and has good stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346124A_ABST
    Figure CN119346124A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a nano copper oxide catalyst, which comprises the following steps: mixing nano copper oxide particles and soluble cerium salt in water, and then carrying out hydrothermal reaction in vacuum or protective atmosphere, so that copper oxide on the surfaces of the nano copper oxide particles is partially reduced into cuprous oxide, and ceric oxide is covered at the same time; ceric ions and cerium ions enter crystal lattices of copper oxide; and then hydrazine is added for further reaction, so that the ceric ions entering the copper oxide crystal lattice are partially reduced into cerium ions, and the multiple crystal lattice distortion of the copper oxide crystal lattice is realized to obtain the nano copper oxide catalyst rich in oxygen vacancies. The invention also provides the nano copper oxide catalyst prepared by the method and the preparation method thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalysts, and in particular to a nano copper oxide catalyst and a preparation method and application thereof. Background Art

[0002] Hydrogen has great potential in promoting the development of fuel cells as a clean energy source to replace fossil energy. However, due to the physical and chemical limitations of hydrogen, issues involving the safe storage and transportation of hydrogen are challenging for this major topic. Compared with gaseous hydrogen storage, in situ hydrogen production using liquid fuels such as methanol (CH3OH), an ideal hydrogen carrier, with high hydrogen storage capacity, can not only achieve safe storage and transportation of hydrogen, but also provide an alternative solution for the application of fuel cell systems. In addition, methanol can be obtained from a variety of sources such as fossil fuels, renewable biomass, and carbon dioxide hydrogenation. Notably, methanol steam reforming (MSR) is an economical and effective method that has attracted widespread interest in the fields of energy chemistry and heterogeneous catalysis due to its reasonable energy utilization, simple process control, and high hydrogen yield under relatively mild reaction conditions.

[0003] In the MSR reaction, it is crucial to evaluate the catalyst activity and product selectivity. Among the various catalysts used in MSR, Cu-based catalysts are more attractive with advantages such as low cost, satisfactory low-temperature activity, and high H2 selectivity. However, due to the low Tammann temperature of Cu (407°C), Cu nanoparticles are prone to agglomeration and sintering as suitable active ingredients. Therefore, an effective way to solve this problem is to select suitable additives (such as SiO2, Al2O3, ZnO and CeO2) to improve the catalytic performance and thermal stability of Cu in Cu-based catalysts. In particular, ceria has the function of inhibiting carbon deposition and reducing byproduct CO in the MSR reaction due to its special redox properties. There are various methods for preparing copper-based catalysts, such as CVD, sol-gel and co-precipitation. However, these methods involve multiple processing steps and the synthesis of the catalysts is quite complicated (such as the addition of specific additives). Therefore, it is more attractive to prepare new and efficient copper-based catalysts for MSR reactions by simple and easy methods. In the prior art, Ce-based nanomaterials can be in-situ grown on the support surface through a hydrothermal reaction in a Ce(NO3)3 solution, which not only increases the specific surface area but also improves the catalytic performance.

[0004] However, simply loading Ce-based nanomaterials on the surface of a carrier still has limited improvement in catalytic performance and also has durability issues. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a highly efficient catalyst for reforming hydrogen.

[0006] The present invention is achieved through the following technical solutions: A method for preparing a reforming hydrogen production catalyst comprises the following steps: Nano copper oxide particles and soluble cerium salt are mixed in water and then subjected to hydrothermal reaction under vacuum or protective atmosphere, so that the copper oxide on the surface of the nano copper oxide particles is partially reduced to cuprous oxide and covered with cerium oxide, and cerium ions and cerium ions enter the copper oxide lattice; then hydrazine is added for further reaction, so that the cerium ions entering the copper oxide lattice are partially reduced to cerium ions, thereby achieving multiple lattice distortions of the copper oxide lattice and obtaining a nano copper oxide catalyst rich in oxygen vacancies.

[0007] The ratio of the nano copper oxide, the soluble cerium salt and the hydrazine is 0.8-1.2 g: 0.08-0.12 mol: 0.04 mol.

[0008] The protective atmosphere includes inert gas or nitrogen.

[0009] The temperature of the hydrothermal reaction is 160-200°C. The ratio of the nano copper oxide to water is 0.8-1.2 g:25 mL.

[0010] The hydrothermal reaction time is 25-35min; The further reaction time is 25-35 min.

[0011] The method for preparing the reforming hydrogen production catalyst further comprises a drying step; The drying temperature is 55-65° C., and the drying time is 20-28 hours.

[0012] The nano copper oxide catalyst is prepared by the method for preparing the reforming hydrogen production catalyst.

[0013] The nano copper oxide catalyst is used in reforming to produce hydrogen.

[0014] The temperature of the reforming hydrogen production is 260-280°C.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention adopts a hydrothermal method to prepare a CeO2-modified nano CuO catalyst. 2+ Reduced to Cu by cerium ions +After that, the cerium ions are oxidized to high cerium ions, so that the surface of the nano-CuO particles is coated with CeO2. At the same time, during this reaction process, high cerium ions also enter the copper oxide lattice. Then hydrazine is added for further reaction, so that the high cerium ions entering the copper oxide lattice are reduced, thereby achieving multiple lattice distortions of the copper oxide lattice, thereby generating a large number of oxygen vacancies. CeO2 is also partially reduced to Ce2O3. The coexistence of CeO2 and Ce2O3 increases the oxygen vacancies on the surface of copper oxide. Ce 4+ and Ce 3+ The CuO lattice regulates the electronic structure of copper oxide and promotes the reforming reaction of Cu + of stability. In addition, after loading high cerium oxide, the specific surface area of ​​nano copper oxide particles will also increase. In addition, CeO2 not only acts as a physical spacer to prevent agglomeration and sintering between Cu elements during the reaction, but also can interact with Cu elements to promote MSR reactions. The CuO-CeO2 catalyst prepared by this method can produce interactions and abundant interfaces and oxygen vacancies between CuO and CeO2, thereby improving the performance of the MSR reaction. Therefore, the nano CuO catalyst prepared by the present invention can achieve a methanol conversion rate of nearly 100% and a CO selectivity of 0.045%, and also has good stability. In contrast, the nano CuO catalyst obtained by hydrothermal treatment without hydrazine has a low methanol conversion rate at 270°C and poor CO selectivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The XRD patterns of the catalysts prepared in Examples 1-4 and Comparative Example 1 are shown; Figure 2 The Raman spectra of the catalysts prepared in Examples 1-4 and Comparative Example 1 are shown; Figure 3 The H2-TPR diagrams of the catalysts prepared in Example 2 and Comparative Example 1 are shown; Figure 4 The Cu 2p spectra in the XPS graphs of SCuO and CuO-Ce3 are shown; Figure 5 The Ce3d in the XPS graphs of SCuO and CuO-Ce3 is shown 5 / 2 Spectrum graph; Figure 6 The O1s spectra in the XPS graphs of SCuO and CuO-Ce3 are shown; Figure 7 (a) FE-SEM, (bc) HRTEM and (dg) EDS spectra of CuO-Ce3 catalyst are shown; Figure 8Shows the HRTEM spectrum of the CuO-Ce3 catalyst; Fig. 9 shows the Fourier transform infrared spectra of CuO-Ce3 catalysts at different reforming reaction times; Fig.10 shows a schematic diagram of the experimental setup; Fig.11 The EPR spectrum of the catalyst oxygen vacancies is shown; Fig.12 (a) The catalytic performance of the structured catalyst at different temperatures; (b) The steady-state performance of the structured catalyst. Reaction conditions: 4 mL / h, H2O / CH3OH = 1.05 molar ratio.

[0017] Fig.13 a shows the XRD patterns of RSCuO and RCuO-Ce2; Fig.13 b shows the XPS patterns of RSCuO and RCuO-Ce2; Fig.13 a shows the LLM diagram of RSCuO and RCuO-Ce2 Fig.14 a shows the SEM of CuO-Ce3 before reaction; Fig.14 b shows the SEM of CuO-Ce3 after reaction; Fig.14 c shows the Raman spectra of CuO-Ce3 before and after the reaction.

[0018] Fig.15 a shows the relationship between the methanol conversion rate of the catalyst and the conversion temperature: Fig.15 b shows the relationship between the CO selectivity of the catalyst and the conversion temperature; Fig.15 c shows the relationship between the H2 selectivity of the catalyst and the conversion temperature; Fig.15 d shows the relationship between the steady-state performance of the catalyst and the conversion temperature; Fig.15 The conversion conditions of ab were as follows: methanol-water gas flow rate was 4 mL / h, wherein the molar ratio of H2O / CH3OH was 1.05. DETAILED DESCRIPTION

[0019] The present invention is further described below in conjunction with specific embodiments.

[0020] The raw materials involved in the specific embodiments of the present invention are as follows: Copper oxide nanoparticles (CuO, 20 nm) were purchased from China Metallurgical New Materials Co., Ltd. Cerium nitrate hexahydrate (Ce(NO3)3·6H2O, purity ≥ 99.5%) was from Macklin. Silica powder (SiO2), methanol (CH3OH), and ethanol were purchased from Shanghai Chemical Reagent Co., Ltd. Cordierite honeycomb ceramics (Φ20×50 mm, 400 cpsi) were purchased from Jiangxi Tianma Industrial Ceramics Co., Ltd. Aluminum sol (20 wt%, binder) was obtained from Suzhou Baird New Materials Technology Co., Ltd. Hydrazine hydrate was purchased from Sigma-Aldrich. All reagents were not further purified.

[0021] The characterization method of the catalyst involved in the specific embodiment of the present invention is as follows: Inductively coupled plasma optical emission spectrometer (ICP-OES, PerkinElmer Avio500, USA) was used to determine the elemental composition of the catalysts. The crystalline phase of the catalysts was detected by X-ray diffractometer (XRD, SmartLab SE, Rigaku, Japan) with a scan range of 10° to 80° (2θ, scan speed: 5° / min). The structure and chemical properties of the prepared catalysts were examined by Raman spectroscopy (ThermoScientific DXR3, USA). The interaction of the catalysts was measured by hydrogen temperature-programmed reduction (H2-TPR, Microtrac BELCat II, Japan). The surface chemical state of the catalysts was studied by X-ray photoelectron spectroscopy (XPS, ThermoScientific K-Alpha, USA) and Auger electron spectroscopy (XAES, Thermo Science K-Alpha, USA). Electron paramagnetic resonance spectroscopy (EPR, Bruker A300, Germany) was performed to examine the oxygen vacancies in the catalysts. The morphology of the catalysts was determined by field emission scanning electron microscopy (FE-SEM, Igmahd, Zeiss, UK). The lattice spacing and element distribution of the catalysts were examined by transmission electron microscopy (TEM, Themis Z, Netherlands) equipped with EDAX energy dispersive X-ray spectroscopy (EDS). Nitrogen adsorption-desorption experiments (ASAP 2460, Micromeritics, USA) were performed to measure the catalysts before and after the reaction, and the specific surface area and pore size distribution of the catalysts were obtained by Brunauer-Emmett-Teller (BET) and Barrett-Joyner-Halenda (BJH) analysis. Fourier transform infrared spectroscopy (FTIR, Thermo Scientific Nicolet iN10, USA) was used to characterize the MSR reaction mechanism on the catalyst surface at 270 °C, and the background of potassium bromide and catalyst was subtracted.

[0022] Example 1 Catalyst preparation 0.04 mol of Ce(NO3)3·6H2O2 was added to 5 mL of deionized water, and then 1 gram of CuO nanoparticles was added to the solution and stirred for 30 minutes. Then, the CuO-containing solution was transferred to a 100 mL Teflon-lined stainless steel autoclave and reacted in a 180°C forced air drying furnace for 12 hours. After cooling to room temperature, 0.01 mol of hydrazine hydrate was added to the stainless steel autoclave and then reacted in a 180°C forced air drying furnace for 5 hours. The nanoparticles were repeatedly centrifuged with deionized water and ethanol, and then dried at 60°C for 24 hours to obtain a catalyst. In the following, the catalyst prepared in Example 1 is referred to as CuO-Ce1.

[0023] Example 2 Catalyst preparation 0.08 mol of Ce(NO3)3·6H2O was added to deionized water, and then 1 gram of CuO nanoparticles was added to the solution and stirred for 30 minutes. Then, the CuO-containing solution was transferred to a 100 mL Teflon-lined stainless steel autoclave and reacted in a 180°C forced air drying furnace for 12 hours. After cooling to room temperature, 0.01 mol of hydrazine hydrate was added to the stainless steel autoclave and then reacted in a 180°C forced air drying furnace for 5 hours. The nanoparticles were repeatedly centrifuged with deionized water and ethanol, and then dried at 60°C for 24 hours to obtain a catalyst. In the following, the catalyst prepared in Example 2 is referred to as CuO-Ce2.

[0024] Example 3 Catalyst preparation 0.12 mol of Ce(NO3)3·6H2O was added to deionized water, and then 1 gram of CuO nanoparticles was added to the solution and stirred for 30 minutes. Then, the CuO-containing solution was transferred to a 100 mL Teflon-lined stainless steel autoclave and reacted in a 180°C forced air drying furnace for 12 hours. After cooling to room temperature, 0.01 mol of hydrazine hydrate was added to the stainless steel autoclave and then reacted in a 180°C forced air drying furnace for 5 hours. The nanoparticles were repeatedly centrifuged with deionized water and ethanol, and then dried at 60°C for 24 hours to obtain a catalyst. In the following, the catalyst prepared in Example 3 is referred to as CuO-Ce3.

[0025] Example 4 Catalyst preparation 0.16 mol of Ce(NO3)3·6H2O was added to deionized water, and then 1 gram of CuO nanoparticles was added to the solution and stirred for 30 minutes. Then, the CuO-containing solution was transferred to a 100 mL Teflon-lined stainless steel autoclave and reacted in a 180°C forced air drying furnace for 12 hours. After cooling to room temperature, 0.01 mol of hydrazine hydrate was added to the stainless steel autoclave and then reacted in a 180°C forced air drying furnace for 5 hours. The nanoparticles were repeatedly centrifuged with deionized water and ethanol, and then dried at 60°C for 24 hours to obtain a catalyst. In the following, the catalyst prepared in Example 4 is referred to as CuO-Ce4.

[0026] Comparative Example 1 Catalyst preparation 0.08 mol of Ce(NO3)3·6H2O was dissolved in 25 mL of deionized water, and then 1 gram of CuO nanoparticles was added to the solution and stirred for 30 minutes. Then, the CuO-containing solution was transferred to a 100 mL Teflon-lined stainless steel autoclave and reacted in a forced air drying furnace at 180°C for 12 hours. After cooling to room temperature, the hydrothermally treated nanoparticles were repeatedly centrifuged with deionized water and ethanol, and then dried at 60°C for 24 hours. In the following, the catalyst prepared in Comparative Example 1 is referred to as SCuO. In the following, the catalyst synthesized in Comparative Example 1 is referred to as SCuO. In addition, SCuO and CuO-Ce3 after 10 hours of reforming reaction are designated as RSCuO and RCuO-Ce3.

[0027] The characterization results of the catalyst prepared in the embodiment of the present invention are as follows: The present invention characterized the elemental composition of the catalysts prepared in Examples 1-5 and Comparative Example 1 by ICP-OES. The results are shown in the following table: Table 1 Element composition of the catalysts prepared in each example As can be seen from the table above, the mass ratio of Cu / (Cu+Ce) decreases with the increase of Ce(NO3)3·6H2O concentration in the hydrothermal reaction. Figure 1 As shown, the present invention characterized the crystalline phase of the catalysts prepared in Examples 1-4 and Comparative Example 1 by XRD. CuO phase (PDF#80-1917) can be observed in all catalysts. As the Ce content increases, it is found that the peaks of CeO2 phase (PDF#75-0120) and CuO gradually become lower.

[0028] The present invention uses Raman spectroscopy to study the structure and chemical properties of the catalysts prepared in Examples 1-4 and Comparative Example 1. Figure 2 It can be seen that 223 and 274cm -1The two peaks near 453 cm-1 correspond to the A1g and Eg modes of CuO, respectively. -1 The peak centered at 600 cm is attributed to the triple simplified F2g vibration mode of CeO2 crystal, while the peak at 600 cm -1 The nearby peaks are related to oxygen defects (D band). The appearance of the D band is due to the formation of defects in the Ce-O coordination, which results in the inability of the Ce-O vibration signal to cancel out in all directions. This shows that there may be a Cu-O-Ce coordination structure in the prepared catalyst. Due to the unequal interaction between Cu-O and Ce-O, there are differences in the vibration of Ce-O in different directions. In addition, with the increase of Ce concentration, the F2g peak of CeO2 red-shifts, indicating that there is a strong interaction between CuO and CeO2, which will lead to changes in the electronic structure and coordination environment of the catalyst.

[0029] In order to further characterize the interaction between CuO and CeO2, the present invention examined the catalyst powders prepared in Example 2 and Comparative Example 1 by H2-TPR. Since CeO2 cannot be reduced below 300°C, the H2 reduction peak of the catalyst is related to CuO. Obviously, due to the addition of Ce element and hydrazine, the reduction peak narrows and moves to a lower temperature, which indicates that the interaction between CeO2 and CuO promotes the reduction of CuO at low temperatures, thus contributing to the improvement of catalytic performance (such as Figure 3 as shown).

[0030] The present invention uses XPS analysis to characterize the surface chemical states of SCuO and CuO-Ce3. Figure 4 As shown, in the Cu 2p spectrum, the peaks around 933.8 and 953.4 eV correspond to Cu 2+ 2p 3 / 2 and 2p 1 / 2 orbital peak, the rest of the peaks belong to Cu 2+ In addition, after the introduction of CeO2, Cu2p 3 / 2 and Cu2p 1 / 2 The peak of the catalyst Ce3d 5 / 2 picture( Figure 5 ) can be seen that there is also Ce in the catalyst 3+ .

[0031] In the MSR reaction, the oxygen-rich vacancies of the catalyst play an important role in the effective activation of H2O and the rapid conversion of C-containing intermediates, thereby increasing the methanol conversion rate and reducing the CO selectivity. The present invention uses XPS and EPR spectra to confirm the changes in the oxygen vacancy concentrations in the catalysts of Example 2 and Comparative Example 1. Figure 6As shown, the O1s spectrum is decomposed into three contribution peaks, which are related to lattice oxygen (about 529.4 eV, OL), oxygen vacancies (about 531.2 eV, OV) and surface chemically adsorbed oxygen (about 532.3 eV, OC). Compared with SCuO, the OV peak area ratio (OV / (OL+OV+OC) of CuO-Ce3 increased from 29.5% to 37.2%. SCuO and CuO-Ce3 have resonance signals at g=2.003 ( Fig.11 ), which is due to the presence of oxygen vacancies. Obviously, the EPR signal of CuO-Ce3 is higher. The stronger the EPR signal, the higher the oxygen vacancy concentration. In addition, the D band appearing on CuO-Ce2 indicates that more oxygen vacancies are formed on CuO-Ce2 compared to SCuO. These results together indicate that the oxygen vacancy concentration in the catalyst increases with the addition of hydrothermally formed CeO2.

[0032] The particle morphology of the catalyst was examined by SEM and TEM. The SCuO catalyst was spherical with a particle size of about 20.3 nm (Figure 7). It is worth noting that during the hydrothermal reaction, CeO2 nanoparticles grew on the CuO surface ( Figure 7 (red circles in b). The lattice spacing of 0.275 nm and 0.312 nm are related to CuO (1 1 0) and CeO2 (1 1 1), respectively, which is consistent with the XRD and Raman results. The EDS spectrum further studied the element distribution of CuO-Ce2. As shown in the spectrum ( Figure 7 dg), the Ce element is distributed on the CuO surface, which indicates that there may be an interaction between CuO and CeO2 due to the obvious contact between the two oxides. In addition, the specific surface area, pore volume and average pore size of the catalysts were determined by N2 adsorption-desorption method (see Table 2). With the introduction of CeO2, the specific surface area of ​​SCuO catalyst increased from 19.9 m 2 / g increased to 31.1m 2 / g, which is because CeO2 nanoparticles with smaller particle size are generated in the hydrothermal reaction. This result is consistent with the above TEM results.

[0033] Table 2 Fourier transform infrared spectroscopy ( Fig. 9 )The MSR reaction mechanism on the CuO-Ce2 catalyst surface at 270℃ was experimentally studied. 3850-3650cm -1 and 1456cm -1 The peak at 3430 cm-1 corresponds to the stretching vibration and symmetric bending of the OH bond of methanol. -1 and 1634cm -1 Nearby. 2919cm-1 、2848cm -1 and 1100-1000cm -1 The peak at 2958 cm-1 is attributed to the methoxy species (CH3O*), which comes from the stretching of CH and CO bonds. The CH stretching vibration, OCO asymmetric and symmetric stretching peaks of the formate species (HCOO*) are located at 2958 cm-1, -1 、1560cm -1 and 1390cm -1 2400-2300cm -1 and 1730 cm -1 The absorption peak of CO2 and the C=O vibration peak of aldehydes (CH2O*) are related. -1 and 1210cm -1 The peaks near 3850-3650cm -1 、2919cm -1 、2400-2300cm -1 、1730cm -1 and 1560cm -1 The peak intensity near the catalyst surface continued to increase, indicating that methanol, CH3O*, CO2, CH2O*, and HCOO* gradually accumulated on the catalyst surface. However, the peak signals of methanol, CH3O*, CO2, CH2O*, and HCOO* remained stable after 6 minutes, indicating that the adsorption of reactants and intermediates on the catalyst surface reached saturation. These results reveal the reaction pathway of MSR as follows: (1) methanol is first dehydrogenated to CH3O*; (2) CH3O* is further dehydrogenated to CH2O*; (3) CH2O* reacts with OH* or O* dissociated from H2O to form HCOO*; (4) HCOO* is finally converted into CO2 and H2.

[0034] The present invention adopts Fig.10 The equipment shown is used to carry out reforming hydrogen production. Specifically, first, 300 mg of the catalyst is mixed with an appropriate amount of SiO2 and compressed into a sheet. Then, the sheet catalyst is transferred to the reforming chamber of a tubular furnace (OTF-1200X, High Frequency-Nanjing, China). A methanol aqueous solution (H2O / CH3OH=1.05 molar ratio) is transported to the evaporation chamber using a peristaltic pump (CT1000, Chuangrui, China). The unreacted reactants are collected by a condensing device, and then the gas products (i.e., H2, CO, and CO2) are detected using a gas chromatograph (GC, SP-7890, China) equipped with TCD and FID. In addition, an electronic soap bubble flowmeter (SCalPlus, China) is also used to measure the gas flow rate. The calculation formulas for methanol conversion and gas product selectivity are as follows: Before loading the catalyst, the cordierite honeycomb ceramics were pretreated. Specifically, they were washed with deionized water and ethanol several times, then dried at 100°C for 12 hours, and finally calcined at 800°C for 4 hours to remove residual organic matter. Then, the CuO-Ce3 catalyst, deionized water, and aluminum sol were added to a nylon jar and then ball-milled for 2 hours (speed: 200rpm / min). Next, the honeycomb ceramics were repeatedly impregnated with the slurry formed by ball milling and then dried at 80°C. After each impregnation, the excess slurry in the honeycomb ceramics was removed by blowing. The catalyst loading was maintained at ~300mg.

[0035] The catalytic performance of the catalysts was then evaluated in a quartz tube reactor for MSR reaction at 210-290°C with a H2O / CH3OH molar ratio of 1.05. As an endothermic reaction (wherein), both methanol conversion and CO selectivity increased with increasing reaction temperature ( Fig.15 ab). The catalyst has a H2 selectivity of about 75% ( Fig.15 c), thereby providing sufficient H2 for the fuel cell system. In addition, under the same reaction conditions, the CO selectivity decreases with the increase of Ce content, which may be due to the increase in oxygen vacancy concentration promoting the dissociation of H2O, thereby accelerating the conversion of CO to CO2 in the water gas shift reaction (WGSR). However, when the Ce content is too high, the methanol conversion rate decreases because the active sites of the Cu species are blocked by CeO2, thereby reducing the contact between the Cu species and the reactants. Therefore, among these catalysts, the CuO-Ce3 catalyst has the best catalytic performance at 270°C, with a methanol conversion rate of 100% and a CO selectivity of 0.045%. Since reaction stability is an important indicator for evaluating catalysts for MSR reactions, the steady-state performance of the CuO-Ce2 catalyst was studied. After 100 hours of reaction, the methanol conversion rate decreased (from 100% to 92.3%), and the CO selectivity remained in the range of 0.036%-0.049% ( Fig.15 d), which indicates that the catalyst has good durability. In order to exclude the influence of silica on the catalytic performance, a blank test was carried out on pure silica flakes under the same reaction conditions, and the results showed no catalytic activity.

[0036] Methanol conversion and gas selectivity of catalyst powder. Reaction conditions: 270 ℃, 4 mL / h, H2O / CH3OH = 1.05 molar ratio.

[0037] Table 3 In practical applications, structured catalysts are increasingly favored for large-scale catalytic reactions due to their low pressure drop and high utilization rate. Therefore, a structured catalyst was formed by coating a CuO-Ce2 catalyst on cordierite, and then the catalytic activity and durability of the structured catalyst in the MSR reaction were studied. The structured catalyst achieved a methanol conversion rate of 100% at 270°C and a CO selectivity of 0.050% ( Fig.12 a). After 100 hours of reaction, the methanol conversion rate dropped from 100% to 92.0%, while the CO selectivity remained in the range of 0.043%-0.051% at 270℃ ( Fig.12 b), which indicates that the catalyst has good stability in long-term reactions. In addition, Table 4 summarizes the catalytic performance of various copper-based catalysts in MSR reactions in the past few years. Compared with these copper-based catalysts, the copper-based catalyst prepared in the present invention exhibits higher activity and lower CO selectivity at 270°C.

[0038] Table 4 Catalyst Reaction temperature (℃) Methanol conversion (%) CO selectivity (%) Ref. Cu-In / SiO2 300 96.1 0.02 [1] CuO-CeO2 270 80 0.13 [2] CuO-ZnO-CeO2-ZrO2 280 99.9 0.29 [3] CeCuZn / CNTs 325 98.3 1.3 [4] (Ni0.2Cu0.8) / BN 320 100 0

[35] CuCeO2 260 100 0.6 [6] Cu-Ce / SBA-15 290 98.5 0.6 [7] CuO-ZnO-ZrO2 / Al2O3 / SiC 280 79.75 -- [8] CuZn / MCM-41 300 88 0.45 [9] 3D structured Cu-based catalyst 280 93.6 0.07

[10] Cu / SiC 280 82.9 --

[11] Cu / ZnO 275 94 3

[12] CuO-Ce3 270 100 ~0.045 This work The literature involved in the above table is as follows: 1. F. Bossola, T. Roongcharoen, M. Coduri, C. Evangelisti, F. Somodi, L. Sementa, A. Fortunelli, V. Dal Santo, Discovering indium as hydrogenproduction booster for a Cu / SiO2 catalyst in steam reforming of methanol, Applied Catalysis B: Environmental 297 (2021) 120398. https: / / doi.org / 10.1016 / j.apcatb.2021.120398. 2. Y. Chen, S. Li, S. Lv, Y. Huang, A novel synthetic route for MOF-derived CuO-CeO2 catalyst with remarkable methanol steam reformingperformance, Catalysis Communications 149 (2021) 106215. https: / / doi.org / 10.1016 / j.catcom.2020.106215. 3、X. Jia, H. Zhang, B. Ren, J. Xie, P. Ge, B. Zhang, Fe–Ni–Ce–Zr-modified CuO–ZnO catalyst for methanol steam reforming, Journal of the EnergyInstitute 110 (2023) 101316. https: / / doi.org / 10.1016 / j.joei.2023.101316. 4、H. Shahsavar, M. Taghizadeh, A.D. Kiadehi, Effects of catalystpreparation route and promoters (Ce and Zr) on catalytic activity of CuZn / CNTs catalysts for hydrogen production from methanol steam reforming,International Journal of Hydrogen Energy 46(13) (2021) 8906-8921. https: / / doi.org / 10.1016 / j.ijhydene.2021.01.010. 5、 A.M. Kovalskii, A.T. Matveev, Z.I. Popov, I.N. Volkov, E.V.Sukhanova, A.A. Lytkina, A.B. Yaroslavtsev, A.S. Konopatsky, D.V. Leybo, A.V.Bondarev, I.V. Shchetinin, K.L. Firestein, D.V. Shtansky, D.V. Golberg, (Ni,Cu) / hexagonal BN nanohybrids – New efficient catalysts for methanol steamreforming and carbon monoxide oxidation, Chemical Engineering Journal 395(2020) 125109. https: / / doi.org / 10.1016 / j.cej.2020.125109. 6、S. Yang, F. Zhou, Y. Liu, L. Zhang, Y. Chen, H. Wang, Y. Tian, C.Zhang, D. Liu, Morphology effect of ceria on the performance of CuO / CeO2catalysts for hydrogen production by methanol steam reforming, InternationalJournal of Hydrogen Energy 44(14) (2019) 7252-7261. https: / / doi.org / 10.1016 / j.ijhydene.2019.01.254. 7、Y. Chen, Y. Huang, Influence of ceria existence form ondeactivation behavior of Cu-Ce / SBA-15 catalysts for methanol steam reforming,International Journal of Hydrogen Energy 48(4) (2023) 1323-1336. https: / / doi.org / 10.1016 / j.ijhydene.2022.10.046. 8、S. Qian, H. Liu, Y. Wang, D. Mei, Structural optimization of 3Dprinted SiC scaffold with gradient pore size distribution as catalyst supportfor methanol steam reforming, Fuel 341 (2023) 127612. https: / / doi.org / 10.1016 / j.fuel.2023.127612. 9、O.O. Fasanya, A.Y. Atta, M.T.Z. Myint, J. Dutta, B.Y. Jibril,Effects of synthesis methods on performance of CuZn / MCM-41 catalysts inmethanol steam reforming, International Journal of Hydrogen Energy 46(5)(2021) 3539-3553. https: / / doi.org / 10.1016 / j.ijhydene.2020.10.181. 10、C. Li, S. Yuan, X. Yao, X. Yu, B. Li, S.-T. Tu, Structurednanoporous copper catalysts prepared by laser powder bed fusion anddealloying for on-board methanol steam reforming, Fuel 347 (2023) 128367.https: / / doi.org / 10.1016 / j.fuel.2023.128367. 11、Y. Wang, H. Liu, D. Mei, S. Yu, Direct ink writing of 3D SiCscaffold as catalyst support for thermally autonomous methanol steamreforming microreactor, Renewable Energy 187 (2022) 923-932. https: / / doi.org / 10.1016 / j.renene.2022.02.004. 12. E. Baydir, Ö. Aras, Methanol steam reforming in a microchannelreactor coated with spray pyrolysis method for durable Cu / ZnO nanocatalyst, Journal of Analytical and Applied Pyrolysis 158 (2021) 105278. https: / / doi.org / 10.1016 / j.jaap.2021.105278. The phases of RSCuO and RCuO-Ce2 catalysts were determined by XRD. Fig.13 a). After 10 h of reforming reaction, all CuO in the sample was reduced to metallic Cu. However, CeO2 in the RCuO-Ce3 catalyst was not reduced, which is consistent with the H2-TPR result. There is no Cu on the catalyst surface after the reaction. 2+ Because with Cu 2+ The satellite peaks (945-940 eV) in the Cu2p spectrum ( Fig.13 b) was not found, indicating that Cu 2+ is completely reduced to Cu0 or Cu + . Since Cu0 and Cu + The difference in binding energy between the two catalysts is not obvious in the Cu2p spectrum. Fig.13 c) Used to confirm Cu 0 and Cu + The CuLMM spectrum of the catalyst is convoluted into four peaks, of which the two peaks at 916.2 and 918.7 eV correspond to Cu + and Cu 0 However, no diffraction peak of Cu2O was detected in the XRD pattern of the catalyst after 10 h of reaction because the catalyst surface was slightly oxidized during the test. After the introduction of CeO2, the Cu + / (Cu + +Cu 0 ) ratio increased from 26.5% to 41.0%. The results show that CeO2, Ce 3+ The interaction with Cu is beneficial to the formation of Cu-O-Ce interface, thus promoting the Cu + The stability of Cu + The increase in the ratio can enhance the synergistic effect between Cu and CeO2, thus promoting the MSR reaction.

[0039] Sintering and carbon deposition are closely related to the deactivation of copper-based catalysts in MSR reactions. In order to study the deactivation factors, the catalysts before and after the reaction were characterized by BET, SEM, and Raman. The CuO-Ce3 catalyst after 100 hours of reforming reaction was named UCuO-Ce3. As can be seen from Table 2, the specific surface area of ​​CuO-Ce3 increased from 31.1 m 2 / g is reduced to 13.2m 2 / g. After 100 hours of reaction, the catalyst particles were significantly enlarged ( Fig.14 ab). In addition, the D band of carbon (about 1360 cm -1 , disordered and defective carbon) or the G band (about 1580cm -1 , well-structured coke or graphite) signal peak ( Fig.14 c). Therefore, sintering and growth lead to the deactivation of CuO-Ce3 catalyst, which may be caused by the migration, aggregation and Ostwald ripening of nanoparticles during the reaction.

[0040] The introduction of Ce species changes the electronic structure of the catalyst and promotes the Cu + The stability of the catalyst was attributed to the interaction between CuO and CeO2. In addition, the oxygen vacancy concentration of the catalyst increased (from 29.5% to 37.2%) and the specific surface area increased (from 19.9 to 31.1 m 2 / g). The results show that the addition of Ce species can improve the catalytic activity of MSR reaction and reduce the selectivity of CO. Therefore, among these catalysts, the CuO-Ce3 catalyst has the best catalytic performance, with a methanol conversion of 100% and a CO selectivity of 0.045% at 270°C. After 100 hours of reaction, the methanol conversion decreased (from 100% to 92.3%), and the CO selectivity remained in the range of 0.036% to 0.049%, which shows that the catalyst has excellent stability. In contrast, the SCuO catalyst can achieve a methanol conversion of 78.1% and a CO selectivity of 0.118% at 270°C. In practical applications, structured catalysts are increasingly favored for large-scale catalytic reactions due to their low pressure drop and high utilization rate. Therefore, the structured catalyst formed by coating the CuO-Ce3 catalyst on cordierite honeycomb ceramics achieved a methanol conversion of 100% and a CO selectivity of 0.050% at 270°C. After 100 hours of reaction, the methanol conversion rate dropped from 100% to 92.0%, and the CO selectivity was 0.043%-0.051%. Fourier transform infrared spectroscopy further elucidated the evolution of reactants and intermediates on the catalyst surface. In addition, sintering and agglomeration are the causes of catalyst deactivation during the MSR reaction.

Claims

1. A method for preparing a nano copper oxide catalyst, characterized in that: The steps include: Nano copper oxide particles and soluble cerium salt are mixed in water and then subjected to hydrothermal reaction under vacuum or protective atmosphere, so that the copper oxide on the surface of the nano copper oxide particles is partially reduced to cuprous oxide and covered with cerium oxide, and cerium ions and cerium ions enter the copper oxide lattice; then hydrazine is added for further reaction, so that the cerium ions entering the copper oxide lattice are partially reduced to cerium ions, thereby achieving multiple lattice distortions of the copper oxide lattice and obtaining a nano copper oxide catalyst rich in oxygen vacancies.

2. The method for preparing a nano copper oxide catalyst as claimed in claim 1, characterized in that: The ratio of the nano copper oxide particles, the soluble cerium salt and the hydrazine is 0.8-1.2 g: 0.08-0.12 mol: 0.04 mol.

3. The method for preparing a nano copper oxide catalyst as claimed in claim 1, characterized in that: The protective atmosphere includes inert gas or nitrogen.

4. The method for preparing a nano copper oxide catalyst as claimed in claim 1, characterized in that: The temperature of the hydrothermal reaction is 160-200°C.

5. The method for preparing a nano copper oxide catalyst as claimed in claim 1, characterized in that: The ratio of the nano copper oxide to water is 0.8-1.2 g:25 mL.

6. The method for preparing a nano copper oxide catalyst as claimed in claim 1, characterized in that: The hydrothermal reaction time is 25-35 minutes.

7. The method for preparing a nano copper oxide catalyst as claimed in claim 1, characterized in that: Also includes a drying step; The drying temperature is 55-65° C., and the drying time is 20-28 hours.

8. The nano copper oxide catalyst prepared by the method for preparing the nano copper oxide catalyst according to any one of claims 1 to 7.

9. The use of the nano copper oxide catalyst as claimed in claim 1, characterized in that: Applied to the reforming of alcohol to produce hydrogen.

10. The use of the nano copper oxide catalyst as claimed in claim 9, characterized in that: The temperature of the reforming hydrogen production is 260-280°C; The alcohols include C1-C5 alcohols.

Citation Information

Patent Citations

  • Preparation method and application of porous material loaded with Cu / ZnO / CeO2 catalyst

    CN113000057A

  • Preparation method and application of cerium oxide loaded copper-based catalyst

    CN117160463A

  • Copper-zinc oxide catalyst and preparation method and application thereof

    CN117531516A

  • Metal oxide support and catalyst, preparation method and its applications.

    PT105613A

  • Catalysts for the production of hydrogen

    WO2010075162A1

Cited By

  • Preparation method and application of copper-loaded cerium oxide catalyst

    CN122209403A